Kirchner and Murnau: Iconic, Thematic and Semantic Recurrences from the Figurative Arts to Cinema (Itinera, 2016)
German Expressionism has had from the beginning a multidisciplinary character and the works of the painters, pertaining to that current, have strongly influenced the filmmakers of the subsequent decade. More specifically, it is possible to find in some sequences of Nosferatu by Friedrich Wilhelm Murnau several formal features that have characterized the production of expressionist Ernst Ludwig Kirchner, as well as the direct quotation of some works of him, including The Red Tower in Halle, Two Women in the Street and Five Women in the Street. The reproduction in the frames of specific works of art, the image distortion, even the make-up of actors resume then aesthetic elements first developed by Murnau and are intended to convey to the viewer a sense of anxiety compared to the reality, to the contemporary society, to the city life, even manifesting an inner struggle, that has united Kirchner and Murnau itself.